Impact of a neuroeducational intervention on factors associated with academic failure and academic performance in medical students. - Estrada Reyes , Nallely Sarahí; Mendoza Anaya, Lorena; Reza López, Sandra Alicia; Fierro Fierro , Omar; Martínez Rodríguez , Carlos Felipe (Spanish Journal of Medical Education, 2026)
Background: Academic performance in medical students is a multifactorial phenomenon influenced by intrinsic and extrinsic factors that may facilitate or hinder learning. Identifying these factors and evaluating neuroeducational interventions may contribute to the development of strategies to enhance academic performance. Objective: To analyze the impact of a neuroeducational intervention on intrinsic factors, extrinsic factors, and academic performance in medical students. Methods: A mixed-methods study was conducted, integrating a qualitative phase and a quantitative quasi-experimental pretest-posttest design with intervention and control groups. The qualitative phase included 47 students with a history of course failure, and the data were analyzed using ATLAS.ti. The quantitative phase included 43 students (27 in the control group and 16 in the intervention group). The intervention group participated in a neurolearning course. Quantitative data were analyzed using pretest-posttest comparisons, with statistical significance set at p< 0.05. Results: Course failure was associated with difficulties in organization, time management, study strategies, and emotions such as anxiety, stress, and nervousness. The intervention group showed a significant improvement in academic emotions (p=0.005) and a significant increase in third-term examination scores compared with both the first (p=0.026) and second examinations (p=0.035). No significant changes were observed in extrinsic factors. Conclusions: The neuroeducational intervention promoted positive changes in intrinsic learning-related factors and was associated with improved academic performance, providing evidence of its potential to enhance the education of medical students.